Formulation of paracetamol tablets using sodium starch glycolate (SSG) derived from pineapple stem starch (Ananas comosus (L.) Merr) as a super disintegrant using wet granulation - Rahayyu, Annisa Maulidia; Novi Andreyani Safitri; Riri Fauziyya; Musa Musa; Novi Kuswardani; Okta Nama Putra (Universitas Ahmad Dahlan, 2025)
The pineapple stem, a byproduct of the pineapple plant, contains a high starch content suitable for conversion into the super disintegrant sodium starch glycolate (SSG). The starch content of pineapple stems can be modified into the super-disintegrant sodium starch glycolate (SSG). This study aims to explore the potential of modified pineapple stem starch as SSG, evaluate its physicochemical characteristics, and determine the optimal tablet. Pineapple stem starch was modified into SSG through crosslinking and carboxymethylation. Tablets were then prepared using the wet granulation method, followed by physical evaluations of tablets (weight and size uniformity, disintegration time, hardness, and friability). Four formulations with varying super disintegrant concentrations were tested: F0 (4% imported SSG, control), F1 (2% pineapple stem SSG), F2 (4% pineapple stem SSG), and F3 (6% pineapple stem SSG). The tablet evaluations for all formulations met standard requirements for each test. The study's results concluded that pineapple stem starch can be modified into SSG, exhibiting a faster swelling ability compared to natural starch. The typical functional groups of SSG appear at peaks of 1410 cm-1, 1411 cm-1, and 1415 cm-1. The best formula, F3, which is based on the physical properties of the tablets, has met the requirements with the fastest disintegration time.